New species and redescriptions of the New Zealand genus Exsul Hutton (Diptera: Muscidae: Coenosiinae) - Barbosa, Leandro Silva; Couri, Márcia Souto (Zootaxa, 2013)
Exsul Hutton (Diptera, Muscidae) is revised and the genus diagnosis is enlarged. The female of Exsul singularis Hutton is described for the first time. The male and female terminalia of all species are described and illustrated. Exsul alfredoi sp. n. is described and illustrated and compared with the other known species. A key to separate the species is given.